Health impact of toxic metals in facial cosmetics used in Calabar, Nigeria - UkoNaku, Julius; E. Inah, Bassey; A. Mowang, Dominic; P. Ugosor, Terngu (International Journal of Pharmacology and Toxicology, 2020)
The present study highlights the health risk factor of heavy metals in cosmetics considering their habitual use in the society today. This safety assessment has become inevitable because of the high demand for these products which has resulted to flooding the markets with low quality cosmetics. Digestion was by 20 mL mixture of nitric acid (HNO3) and hydrogen peroxide (H2O2) in the ratio of 3:1 and was heated in a hot plate for 2-3 hours at 90 °C. The choice of this mixture was informed by literature to yield the highest amounts in metal digestion. The mean metal concentrations of these products are; 1.2758, 0.9599, 0.1262, 0.0504 and 0.0068 mg/kg while the ranges are: 0.140-5.823, 0.054-3.908, 0.021-0.820, 0.028-0.071 and 0.001-0.236 mg/kg respectively for Mn, Ni, Cr, Cd and Pb. From the analysis, 40 %, 74.28 %, and 17.14 % of the products has Cd, Ni and Mn respectively exceeded the standard. Pb was not detected in majority of the products. Though cosmetic safety cannot be ascertained only by their heavy metal content, the present paper focuses solely on the contribution of heavy metals as a risk factor to the consumption of these products.